POTENTIAL DEVELOPMENT OF RURAL TOURISM IN PENATIH VILLAGE - I Wayan Pantiyasa; Ni Luh Supartini (Journal of Business on Hospitality and Tourism, 2016)
The development of tourism in Bali has a real effect on economy in Bali. Development and promotion of tourism that has been done should be capable to be sustained and maintained in the future. Tourism sustainability discourse must involve the commitment from all parties to maintain the sustainability of the natural, social, economic and cultural community as the basic capital of tourism. Tourism Department of Denpasar city is trying to develop the alternative tourism for reducing the negative effects of mass tourism and empowering rural communities through the development of rural tourism. One of the villages targeted is Penatih village which is a village that has the potential resources to be developed into a rural tourism with traditional culture (art), social order, Subak and other.The approach used in this research was qualitative descriptive. The data were collected through interview, observation, documentation and conduct Focus Group Discussion (FGD). Then the data were analyzed by using SWOT analysis. From the result of study, there were found some potential that can be developed and packaged in rural tourism. And also this research provides the strategies to develop this village to be a rural tourism